2018
DOI: 10.1108/ijbm-06-2016-0085
|View full text |Cite
|
Sign up to set email alerts
|

Do the competitors affect cross-buying decisions?

Abstract: Purpose Understanding the effect of competitor’s marketing activities as well as analyzing the impact of one’s own marketing activities is equally important. The purpose of this paper is to determine the role of competing bank’s marketing activities (i.e. competitor’s price and product variety) and main bank’s characteristics (bank’s reputation and expertise) in the cross-buying intentions of customers by studying the interrelationships among these. Design/methodology/approach This study has adopted a hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
5
0
1
Order By: Relevance
“…In relation to "PV", Arora and Aggarwal (2018) confirmed in their cross-sectional study that a combination of convenience, price and variety options positively impacts Indian women's shopping behavior in online environments. Vyas et al (2018) confirmed that consumers bear in mind competitor prices and variety offered before coming to a buying decision. Based on the above, we hypothesize the follows:…”
Section: Stimulus-organism-response (S-o-r) Theorymentioning
confidence: 58%
“…In relation to "PV", Arora and Aggarwal (2018) confirmed in their cross-sectional study that a combination of convenience, price and variety options positively impacts Indian women's shopping behavior in online environments. Vyas et al (2018) confirmed that consumers bear in mind competitor prices and variety offered before coming to a buying decision. Based on the above, we hypothesize the follows:…”
Section: Stimulus-organism-response (S-o-r) Theorymentioning
confidence: 58%
“…Competitor's price Vyas et al (2018), Hati et al (2020) Competing banks that provide attractive offers in economic terms lead consumers to switch because the offer can provide substantial cost savings over time Perceived convenience Ngobo (2003), Ghamry and Shamma (2020), Zhao et al (2022) If consumers are inconvenienced due to location, operating hours, and waiting times of their banks, they will consider switching Effective competitor advertising Zhao et al (2022) Competing banks attract customers through advertisements, campaigns and offers Source(s): Created by author Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…Competitor's price is another example of influential trigger (Vyas et al, 2018). As products and services within the retail banking industry are largely homogenous in nature, price becomes a key aspect for banks to compete for customer acquisition and retention.…”
Section: Determinants Of Switching Behavior In the Banking Industrymentioning
confidence: 99%
“…Moreover, information on competitor’s offers could place our results into perspective. As emphasized by Vyas Roy and Raitani ( 2018 ) in bank sector, competitor’s price plays a role onto customers cross-buying intentions more than the reputation and expertise of the primary bank.…”
Section: Conclusion and Discussionmentioning
confidence: 99%